PENGARUH PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA UMKM ROJO SOSIS DI RT 03 RW 06 KELURAHAN CIKIWUL, BEKASI TIMUR - Aulia Januar (Institut Bisnis Muhammadiyah Bekasi, 2022)
This study aims to determine and analyze the effect of promotional strategies on consumer buying interest at UMKM Rojo Sosis in Bantar Gebang Cikiwul rt 03. The sampling technique is determined by random sampling by distributing 105 questionnaires to consumers who come and buy. The analytical method used is the statistical analysis method consisting of simple linear regression analysis, simultaneous significance testing (f test), partial significance testing (t-test), and testing the coefficient of determination (R2). The results of this study indicates that there is a positive and significant influence variable service influence (X) on Customer Satisfaction (Y) UMKM Rojo Sosis in di RT 03 RW 06 Kelurahan Cikiwul, Kecamatan Bantar Gebang Kota Bekasi